Microcognitive science: bridging experiential and neuronal microdynamics - Petitmengin, Claire; Lachaux, Jean-Philippe (Frontiers in Human Neuroscience, 2013)
Neurophenomenology, as an attempt to combine and mutually enlighten neural and experiential descriptions of cognitive processes, has met practical difficulties which have limited its implementation into actual research projects. The main difficulty seems to be the disparity of the levels of description: while neurophenomenology strongly emphasizes the micro-dynamics of experience, at the level of brief mental events with very specific content, most neural measures have much coarser functional selectivity, because they mix functionally heterogeneous neural processes either in space or in time. We propose a new starting point for this neurophenomenology, based on a) the recent development of human intra-cerebral EEG research to highlight the neural micro-dynamics of human cognition, with millimetric and millisecond precision and b) a disciplined access to the experiential micro-dynamics, through specific elicitation techniques. This lays the foundation for a microcognitive science, the practical implementation of neurophenomenology to combine the neural and experiential investigations of human cognition at the subsecond level.